Bob1 limits cellular frequency of T‐follicular helper cells. Issue 6 (3rd May 2016) - Yamashita, Keiji; Kawata, Koji; Matsumiya, Hiroshi; Kamekura, Ryuta; Jitsukawa, Sumito; Nagaya, Tomonori; Ogasawara, Noriko; Takano, Ken‐ichi; Kubo, Terufumi; Kimura, Sachiko; Shigehara, Katsunori; Himi, Tetsuo; et al.
Abstract : The transcription coactivator Bob1 is highly expressed in Tfh cells of humans and mice. Results obtained from experiments using Bob1 −/− mice suggest that Tfh cells possess a Bob1‐associated mechanism to restrain their own cell numbers against stimuli of the TCR and CD28. Abstract : T follicular helper (Tfh) cells are involved in specific humoral immunity at initial and recall phases. The fact that the transcription repressors B‐cell lymphoma‐6 and Blimp‐1 determine lineages of Tfh cells and other types of effector CD4 + T cells, respectively, suggests that there are unique mechanisms to establish Tfh‐cell identity. In this study, we found that Tfh cells preferentially express the transcriptional coactivator Bob1. Bob1 of Tfh cells was dispensable for the expression of B‐cell lymphoma‐6 and the functional property of the cells for B cell help. However, upon initial immunization of foreign antigens, the percentages of Tfh cells in Bob1 −/− mice were much higher than those in wild‐type (WT) mice. In addition, expansion of Tfh cells within Bob1 −/− CD4 + T cells transferred into WT mice revealed that the high frequency of Tfh cells was caused by a T‐cell‐intrinsic mechanism. These findings were further supported by the results of in vitro studies demonstrating that Bob1 −/− Tfh cells had greater proliferative activity in response to stimuli by CD3/CD28 monoclonal antibody and were also refractory to CD3‐induced cell death in comparison to WT Tfh cells. These results suggest that Tfh cells harbor a Bob1‐related mechanism to restrict numerical frequency against stimulation of TCRs.